As exortações pós-sinodais familiaris consortio e amoris laetitia : continuidade e descontinuidade no cuidado pastoral às famílias em situação irregular - Velho, Jonas Emerim (2021)
The present work proposes to draw a parallel between the Exhortation Familiaris Consortio and the Exhortation Amoris Laetitia, to perceive the continuity and discontinuity between them with regard to pastoral care for families in a situation called irregular. The research will first present the theology of marriage of both Exhortations, then it will highlight the guidelines of the two documents for family pastoral care and especially for difficult cases, and finally, the continuity and novelty between them will be analyzed starting from, mainly, pastoral graduality and discernment of conscience. It is hoped that this research will help the Church to be merciful and to faithfully fulfill its saving mission.